1999
DOI: 10.1191/026921699674259562
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of using postal questionnaires to examine carer satisfaction with palliative care: a methodological assessment

Abstract: This paper reports on the methodological findings from a project which examined the feasibility of using a postal questionnaire to assess lay carer satisfaction with palliative care. The focus of this paper is the process of questionnaire development and its psychometric evaluation. The questionnaire was derived from an interview schedule used in previous national surveys of care for the dying, and was refined through qualitative work with recently bereaved lay carers. It was then tested in a postal survey of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…Nevertheless, it is worth noting that the response rates (56% in phase I and 65% in phase II), were higher than in previous population-based and service-based surveys. 18,19 The study provides important new evidence that although engaging in mortality follow-back surveys can evoke distressing emotions to some bereaved relatives, many find it a positive and useful experience. This finding has implications for the perceived vulnerability of this group and the ethical debate about engaging them in research.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, it is worth noting that the response rates (56% in phase I and 65% in phase II), were higher than in previous population-based and service-based surveys. 18,19 The study provides important new evidence that although engaging in mortality follow-back surveys can evoke distressing emotions to some bereaved relatives, many find it a positive and useful experience. This finding has implications for the perceived vulnerability of this group and the ethical debate about engaging them in research.…”
Section: Discussionmentioning
confidence: 96%
“…These studies and our pilot study have indicated that most bereaved relatives welcome the opportunity to make a contribution towards improving care for others by taking part in research. Furthermore, using postal surveys of bereaved relatives is a well established and accepted method of research in end-of-life care, with tradition in the UK and indeed recommended in the recent National End of Life Care Strategy[14,22,23]. It has been shown that this kind of surveys can be carried out in an ethical manner.…”
Section: Methodsmentioning
confidence: 99%
“…In one study, response rates were improved by 20% by means of sending one reminder, although ethical concerns caution against further reminders being sent (Jacoby et al 1999). For example, postal questionnaires are an economical method of covering a wide geographical area, avoid interviewer bias, and have also been used to gain good-quality retrospective data from bereaved carers.…”
Section: Methodological Approachesmentioning
confidence: 99%
“…Some argue that seeking the retrospective views of bereaved relatives is one way of overcoming the difficulties of accessing patient views (Jacoby et al 1999;Krishnasamy 2000b). Some argue that seeking the retrospective views of bereaved relatives is one way of overcoming the difficulties of accessing patient views (Jacoby et al 1999;Krishnasamy 2000b).…”
Section: Methodological Issues and Challengesmentioning
confidence: 99%
See 1 more Smart Citation